Perpustakaan Terapung Danau Mawang Dengan Pendekatan Desain Tropis - Julianto Widayat; Muhammad Syarif; Andi Yusri; Aris Sakkar Dollah; Sahabuddin Latif; Khilda Wildana Nur (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
The tropical architectural design approach is one of the concepts that can be applied to buildings that are oriented toward low climate conditions. The tropical climate is characterized by temperature (heat), humidity, and high rainfall. The location of this research is in the western part of Lake Mawang, Jalan Poros Macanda Biring Balang, Mawang Village, Somba Opu District, Gowa Regency, South Sulawesi Province. The purpose of the research is to design a floating library building that can be a place for education, recreation, as well as tourism by taking into account the climate and site conditions using a tropical design. The research method used is direct observation and then analyzes the potential of the site, building, and space, as well as the utilities used. The design results obtained a floating library with an area of ​​5000 m2, building 4951 m2 which is divided into public, semi-public, and private zones. the characteristics of the building using the shape of the roof made sloping 300, the position of the building extends from east to west, the window opening has 2 x 1.8 m2 for, the use of aluminum material, ribbed glass on the facade of the building, porcelain ceramics on the floor of the building, the use of bright colors namely red, blue, green, green with palm vegetation, squirrel tails, cypress, lotus, teh-tehan, the amount of space required is 4951 m2, the site conditions are supported by educational and transportation facilities, the shape of the building is analogous to the philosophical approach of a ship, the site plan consists of the main building, RTH, and RTB. The conclusion of this study shows the characteristics of the floating library building design using a tropical design approach from the shape of the roof, building position, openings, materials, vegetation, space requirements, site analysis, building form, and site plan layout. The implication of this building is expected to be able to support the needs and expectations of users according to the local climate.